Composition and Diversity of Ichthyofauna in an Aquatic Ecosystem in Central Kerala, India - Swapna, S. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2025)
Western Ghat region of India is one of the eight biodiversity “hotspot” regions of the world and Western Ghat rivers are gold mines of fresh water fish fauna. At present faunal diversity of Western Ghat is threatened by anthropogenic activities. This paper provides information on the diversity of fish fauna in a South Western Ghat river system. River Achenkovil is a perennial river originating from South Western Ghat region and flows through Central Kerala. The present fish survey in the river system revealed the presence of 7 orders, 18 families and 52 species. Cypriniformes accounts for 48.07% of total fauna followed by Perciformes (23.08%), Siluriformes (17.30%). Clupeiformes, Cyprinodontiformes, Beloniformes and Synbranchiformes were represented by less than 5% of total fauna. According to IUCN Red List, 2 species (Vulnerable), 3 (Near Threatened), 3 (Endangered). Out of 52 species of fishes 29 are ornamental fishes. River system has rich and diverse fish fauna which is under the threat of anthropogenic activities.